Piezoelectric driving fiber and preparation method and application thereof

By developing piezoelectric chemical driving fibers with high and low voltage composite driving functions, the problems of high driving voltage, weak structural stiffness and slow response speed in the existing technology are solved, and the driving functions of low voltage, low energy consumption, and large output displacement are realized, improving the driving functions of low voltage, low energy consumption, and large output displacement. The mobility and response speed of the projectile body are achieved.

CN119420201APending Publication Date: 2025-02-11XIAN CHANGFENG ELECTROMECHANICAL RES INST
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411655746.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

In the prior art, polymer twisted artificial muscle fibers have high driving voltage, weak structural stiffness, small output strain and driving force of the drive mechanism, and slow response speed, making it difficult to meet the control needs of high maneuverability and fast response of the elastic body.

Method used

Provide a piezoelectric chemical driving fiber with high and low voltage composite driving function, with ion embeddable effect and piezoelectric effect, and can realize electrical energy-chemical reaction-mechanical deformation under the action of -3V~3V driving voltage High-efficiency conversion to realize low voltage, low energy consumption, and large output displacement driving functions.

Benefits of technology

It realizes low voltage, low energy consumption, and large output displacement driving functions, improves response speed, control accuracy and driving force, and meets the high maneuverability and fast response control requirements of the bullet body.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119420201A_ABST
    Figure CN119420201A_ABST
Patent Text Reader

Abstract

The invention discloses piezoelectric electrochemical driving fibers and a preparation method and application thereof, and relates to the technical field of piezoelectric fibers. The fiber is of a rod-shaped concentric roll layer structure and is formed by stacking two or more layered fiber films around the center of an arrangement layout at equal intervals or equal angles and then rolling and twisting the layered fiber films along diagonal lines of the arrangement layout. Or two or more linear fibers with the same length are rotationally twisted along the arrangement center to form the fiber with the spiral structure. The piezoelectric electrochemically driven fiber provided by the invention has a high-low voltage composite driving function, and has both an ion embeddable effect and a piezoelectric effect; high-efficiency conversion of electric energy-chemical reaction-mechanical deformation can be realized based on electrochemical reaction under the action of-3V-3V driving voltage, and a low-voltage, low-energy-consumption and large-output displacement driving function is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of piezoelectric fibers, and in particular to a piezoelectric chemical drive fiber and a preparation method and application thereof. Background Art

[0002] At present, the attitude and orbit control technology used for launch vehicles, missiles, warheads and spacecraft mainly relies on the direct lateral force system, rudder and wing devices and the coupling effect between the two. Among them, solid / liquid / gel / solid-liquid hybrid attitude and orbit control engines face technical difficulties such as short control time, prominent contradiction between the control torque and the carried fuel, and interference between the lateral jet and the airflow of the aerodynamic surface of the missile body. The rudder and wing devices have the disadvantages of ablation and difficulty in functioning outside the atmosphere. Therefore, it is urgent to develop an attitude and orbit control technology with a new working mechanism and control mode.

[0003] In order to achieve accurate terminal interception of medium- and short-range air-to-air missiles by fighter jets, the U.S. Air Force launched the Barrel-Launched Adaptive Monition (BLAM) program in 1997. It uses two pairs of vertical piezoelectric keys to differentially drive the warhead deflection to control the flight trajectory of the missile. However, the piezoelectric keys have small deformation and low technical reliability, which greatly limits the maneuverability and service life of such missiles. Therefore, there is an urgent need to develop a new fast-response and lightweight engine drive technology.

[0004] In the field of new attitude and orbit control power technology, Fu Sen et al. (CN202211589727.9) achieved the ability to adjust the center of mass of the missile by driving the weight slider at the center of mass of the cruise missile through artificial muscle fibers made of twisted polymer fiber materials; Chen Sen et al. (CN201710787823.7) controlled the relaxation and contraction of artificial muscle fibers by regulating the deformation of liquid metal; Liu Zunfeng et al. (CN202211142081.X) and Di Jiangtao et al. (CN20221 0874035.2, CN202111545169.1, CN202210495760.9, CN202010211886.X) formed artificial muscle fibers with a spiral structure by curling / folding, plying and twisting; Lv Jiuan and Hu Zhiming (CN202110575784.0) used a threaded mold to mold and stretch the liquid crystal elastomer to achieve contraction, bending, torsion, winding and variable pitch deformation modes. However, the driving voltage required for these works is high, the structural stiffness is weak, the output strain and driving force of the driving mechanism are small, and the response speed is slow, which makes it difficult to meet the high mobility and fast response control requirements of the projectile. In addition, Di Jiangtao et al. (CN202010257817.2) prepared piezoelectric chemical fibers by twisting conductive fibers and coating gel electrolytes on their surfaces, which generated electrical signals under the action of external mechanical excitation signals. However, this work aims to realize flexible nano-power generation or self-powered sensing technology by utilizing the positive piezoelectric effect. Therefore, the field of attitude and orbit control power technology urgently needs to develop a new engine drive technology with fast response speed, large driving force and large output deformation. Summary of the invention

[0005] In view of the deficiencies in the above-mentioned background technology, the present invention mainly solves the technical problems of high driving voltage, weak structural rigidity, small output strain and driving force of the driving mechanism, slow response speed, etc. of the polymer twisted artificial muscle fiber described in the background technology. The present invention provides a piezoelectric chemical driving fiber and its preparation method and application. The piezoelectric chemical driving fiber has a high-low voltage composite driving function, and has both ion embeddability effect and piezoelectric effect; it can realize efficient conversion of electrical energy-chemical reaction-mechanical deformation based on electrochemical reaction under the action of -3V~3V driving voltage, and realize low voltage, low energy consumption, and large output displacement driving function.

[0006] The first purpose of the present invention is to provide a piezoelectric chemical drive fiber with high and low voltage composite drive function, which has both ion embeddability effect and piezoelectric effect; it can realize efficient conversion of electric energy-chemical reaction-mechanical deformation based on electrochemical reaction under the action of -3V~3V driving voltage, and realize low voltage, low energy consumption, and large output displacement driving function; it can realize rapid conversion of electric energy-mechanical deformation based on inverse piezoelectric effect under the action of -20V~-3V and 3V~130V driving voltage, and realize high precision, fast response, large output force, and displacement ratio adjustment driving function.

[0007] Preferably, the fiber comprises two or more sheets of layered fiber films which are stacked at equal distances or angles around the center of the arrangement and twisted along the diagonal of the arrangement to form a rod-shaped concentric layer structure; Or a fiber with a helical structure formed by two or more linear fibers of equal length being twisted and rotated along the center of arrangement.

[0008] Preferably, the initial length of the fibers in the rod-like concentric coiled layer structure or the fibers in the linear fiber spiral structure is 1-150 cm, and the ratio of the deformed length to the initial length is (0.65-1.05):1.

[0009] Preferably, the layered fiber film includes a substrate and a driving active material attached to the substrate, and the substrate and the driving active material are tightly connected via a heterogeneous structure; the thickness ratio of the driving active material to the substrate is (0.7~2):1.

[0010] Preferably, the driving active material generates electrochemical driven deformation and reverse piezoelectric driven deformation under the action of an applied voltage, and the substrate does not generate deformation response to the applied voltage; the interaction between the substrate and the driving active material causes the rod-shaped concentric coiled layer structure to shrink, and after the applied voltage is removed, the structure returns to its original length; The substrate is a metal foil; the driving active material is a transition metal sulfide.

[0011] Preferably, the linear fiber comprises a polymer fiber and a driving active coating attached to the surface of the polymer fiber; The polymer fiber and the driving active coating are tightly connected via a heterogeneous structure; The polymer fiber has a diameter of 2 mm to 8 mm; The driving active coating has a thickness of 1 μm to 3 μm; The length of the linear fiber changes under the action of an external voltage, so that the fiber with a helical structure is driven to deform in the axial direction; wherein the driving active coating is a transition metal sulfide coating.

[0012] Preferably, when the layered fiber film is twisted or the equal-length linear fibers are twisted, electrolyte gel layers need to be attached to the front and back of the film; the electrolyte gel layers include sulfuric acid gel or ion gel.

[0013] The second object of the present invention is to provide a method for preparing a piezoelectric chemically driven fiber, comprising the following steps: A metal foil with a thickness of 6 μm to 10 μm is fixed on a rotating table in a vacuum chamber, and an inverted transition metal sulfide target is suspended opposite to the metal foil so that the target and the exposed surface of the metal foil are arranged facing each other with a spacing of 30 mm to 45 mm; the transition metal sulfide target is bombarded with a YAG pulse laser with a frequency of 1 Hz to 10 Hz to achieve a solid-plasma-solid phase transition and then deposited on the exposed surface of the metal foil for a deposition time of 10 h to 20 h; a transition metal sulfide film is obtained on the metal foil; 0.5 mol to 1 mol sulfuric acid-polyvinyl alcohol gel or 1-butyl-3-methylimidazolium hexafluorophosphate-polyvinylidene fluoride-hexafluoropropylene ion gel is uniformly coated on the transition metal sulfide film by using a coating machine with a rotation speed of 500 rpm to 10000 rpm; Then, 2 to 50 transition metal sulfide films coated with sulfuric acid-polyvinyl alcohol gel or 1-butyl-3-methylimidazolium hexafluorophosphate-polyvinylidene fluoride-hexafluoropropylene ion gel are stacked and arranged at equal angles along the center of the layout, and the films are twisted at a twist rate of 20 turns / m to 100 turns / m along the diagonal line of the arrangement layout; Subsequently, the rod-shaped concentric coiled layer structure fiber is immersed in 0.5 mol~1 mol sulfuric acid-polyvinyl alcohol gel or 1-butyl-3-methylimidazole hexafluorophosphate-polyvinylidene fluoride-hexafluoropropylene ion gel for 1h~2h, and then solidified in a 5℃~10℃ low-temperature box for 0.5h~1h to obtain a rod-shaped concentric coiled layer structure piezoelectric chemical drive fiber.

[0014] The third object of the present invention is to provide a method for preparing a piezoelectric chemically driven fiber, comprising the following steps: Pour polyacrylonitrile or polyimide spinning stock solution into a decorating bag, select a decorating nozzle with the same outlet size according to the size of the original silk and place it at the front end of the decorating bag, squeeze the decorating bag to spray into a coagulation bath with a concentration of 30% to 60% and a temperature of 40°C to 65°C, and the silk is radially arranged spirally from the center of the coagulation bath to the outside; draw 3 to 5 times in a steam environment of 70°C to 80°C, and then perform a dense treatment in a high-temperature drying box of 85°C to 120°C for 2h to 5h to achieve the shaping of the original silk; The precursor is placed on a rotating table in a vacuum chamber, and an inverted transition metal sulfide target is suspended opposite to the precursor, so that the target and the precursor are arranged facing each other with a spacing of 40mm to 55mm; the transition metal sulfide target is bombarded with a YAG pulse laser with a frequency of 1Hz to 10Hz to achieve a solid-plasma-solid phase transition and then deposited on the exposed surface of the precursor for 8h to 15h; transition metal sulfide is obtained on the surface; Then, the vacuum chamber was opened, the coiled raw silk was turned over, and the vacuum degree was pumped down to 1×10 -7 Torr~7×10- 7 Torr, using a YAG pulse laser with a frequency of 1Hz~10Hz to bombard the transition metal sulfide target for 8h~15h; then take out the original silk with transition metal sulfide growing on the surface, cut it into silk segments with a length of 1cm~150cm, soak it in 0.5mol~1mol sulfuric acid-polyvinyl alcohol gel or 1-butyl-3-methylimidazole hexafluorophosphate-polyvinylidene fluoride-hexafluoropropylene ion gel for 1h~2h, and then solidify it in a 5℃~10℃ incubator for 0.5h~1h; 2 to 50 raw fibers coated with sulfuric acid-polyvinyl alcohol gel or 1-butyl-3-methylimidazolium hexafluorophosphate-polyvinylidene fluoride-hexafluoropropylene ion gel are arranged along the axis to form a raw fiber cluster, two ends of the raw fiber cluster are fixed respectively by two chucks, and a pre-stretching force is applied while twisting at a twist of 100 turns / m to 15,000 turns / m; Subsequently, the helical structure fiber is immersed in 0.5 mol~1 mol sulfuric acid-polyvinyl alcohol gel or 1-butyl-3-methylimidazole hexafluorophosphate-polyvinylidene fluoride-hexafluoropropylene ion gel for 1h~2h, and then solidified in a 5℃~10℃ incubator for 0.5h~1h to obtain a piezoelectric chemically driven fiber with a helical structure.

[0015] A fourth object of the present invention is to provide an application of a piezoelectric chemical drive fiber in an aircraft or a drive mechanism.

[0016] Compared with the prior art, the present invention has the following beneficial effects: The present invention provides a piezoelectric chemical drive fiber and a preparation method and application thereof. The piezoelectric chemical drive fiber can realize a high-low voltage composite drive function, that is, it realizes piezoelectric drive under high voltage conditions and electrochemical drive under low voltage conditions. It can provide a fast-response driving force for the seeker and center-of-mass counterweight slider of a micro-missile and the swing nozzle of the main engine, thereby realizing missile body attitude control and thrust vector control.

[0017] The high- and low-voltage composite driving function of the piezoelectric chemical drive fiber provided by the present invention can simultaneously achieve a significant improvement in output displacement, response speed and control accuracy, reduce the mass and volume of the drive mechanism, and contribute to the development and application of attitude and orbit control power systems.

[0018] The piezoelectric chemical drive fiber provided by the present invention has a simple preparation process, high product stability and durability, and low cost. Most of the equipment required is domestic general equipment, and the preparation threshold is relatively low.

[0019] The preparation method of the present invention can meet the needs of large-scale preparation, thereby achieving a significant reduction in preparation costs, and can also ensure the mass production and delivery of piezoelectric chemical drive fibers. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 Schematic diagram of the preparation process of rod-shaped concentrically rolled laminated electrochemically driven fibers; Figure 2 It is a schematic diagram of stacking and twisting of layered fiber films; Figure 3 This is a scanning electron microscope image of sulfuric acid-polyvinyl alcohol gel; Figure 4 A schematic diagram of a drive fiber mechanism for controlling the attack angle of a micro-projectile seeker; Figure 5 Schematic diagram of the preparation process of linear fiber helical piezoelectric chemical driven fiber; Figure 6 This is a schematic diagram of the spiral radial arrangement of the spinneret; Figure 7 Schematic diagram of twisting and electrification deformation of the original silk cluster; Figure 8 Schematic diagram of using piezoelectric chemical drive fiber to drive the mass slider at the center of mass of the warhead to realize the missile attitude and trajectory control function; Fig. 9 Schematic diagram of the swing nozzle fiber drive mechanism. DETAILED DESCRIPTION

[0021] In order to enable those skilled in the art to better understand and implement the technical solution of the present invention, the present invention is further described below in conjunction with specific embodiments and drawings, but the embodiments are not intended to limit the present invention.

[0022] The purpose of the present invention is to provide a piezoelectric chemical drive fiber, a preparation method and its application, aiming at the construction of ultra-long-range, large-airspace and wide-speed maneuverable flight capability, and to develop a lightweight, fast-response new engine drive technology that can realize attitude control during the flight of a micro-projectile.

[0023] In order to achieve the above-mentioned object, the first aspect of the present invention provides a piezoelectric chemical driving fiber, comprising two or more sheets of layered fiber films stacked at equal distances or equal angles around the center of the arrangement layout, and twisted along the diagonal line of the arrangement layout to form a rod-shaped concentric winding layer structure; Or a fiber with a helical structure formed by two or more linear fibers of equal length being twisted and rotated along the center of arrangement.

[0024] The piezoelectric chemical drive fiber provided by the present invention has a high-low voltage composite drive function, and has both ion embeddability effect and piezoelectric effect; it can realize efficient conversion of electric energy-chemical reaction-mechanical deformation based on electrochemical reaction under the action of -3V~3V driving voltage, and realize low voltage, low energy consumption, and large output displacement driving function; it can realize rapid conversion of electric energy-mechanical deformation based on inverse piezoelectric effect under the action of -20V~-3V and 3V~130V driving voltage, and realize high precision, fast response, large output force, and displacement ratio adjustment driving function.

[0025] The present invention controls the response speed, deformation amplitude, maximum control accuracy, driving force and proportional adjustment characteristics of the driving fiber by regulating the amplitude and waveform of the driving voltage.

[0026] The initial length of the fibers in the rod-shaped concentric coiled layer structure or the fibers in the linear fiber spiral structure is 1-150 cm, and the ratio of the deformed length to the initial length is (0.65-1.05):1.

[0027] According to the present invention, the layered fiber film includes a substrate and a driving active material attached to the substrate, and the substrate and the driving active material are tightly connected through a heterogeneous structure; the thickness ratio of the driving active material to the substrate is (0.7~2):1.

[0028] The driving active material generates electrochemical driven deformation and reverse piezoelectric driven deformation under the action of an applied voltage, and the substrate does not generate deformation response to the applied voltage; the interaction between the substrate and the driving active material causes the rod-shaped concentric coiled layer structure to shrink, and after the applied voltage is removed, the structure returns to its original length; The substrate is a metal foil; the driving active material is a transition metal sulfide.

[0029] According to the present invention, the linear fiber comprises a polymer fiber and a driving active coating attached to the surface of the polymer fiber; The polymer fiber and the driving active coating are tightly connected via a heterogeneous structure; The polymer fiber has a diameter of 2 mm to 8 mm; The driving active coating has a thickness of 1 μm to 3 μm.

[0030] The length of the linear fiber changes under the action of an external voltage, so that the fiber with a helical structure is driven to deform in the axial direction; wherein the driving active coating is a transition metal sulfide coating.

[0031] In one embodiment, the layered fiber film is a heterogeneous structure, which is composed of a driving active material having both ion embedding effect and piezoelectric effect and a substrate material without ion embedding effect and piezoelectric effect. The heterogeneous structure is tightly connected, and no interface debonding occurs during deformation. The thickness ratio of the driving active material and the substrate material is (0.7~2):1. The driving active material can produce electrochemically driven deformation and inverse piezoelectrically driven deformation under the action of an external voltage, while the substrate material does not produce a deformation response to the applied voltage. The interaction between the two causes the rod-shaped concentric coil structure to shrink, and after the external voltage is removed, the structure returns to its original length.

[0032] The equal-length linear fibers are composed of an internal polymer fiber core and an external driving active coating; the heterogeneous interface is tightly bonded and no debonding occurs during deformation; the polymer fiber core has only piezoelectric effect, while the driving active coating has both ion embeddability effect and piezoelectric effect; it can simultaneously produce electrochemical driven deformation and inverse piezoelectric driven deformation under the action of an external voltage; the cross-sectional diameter of the fiber core is 2mm~8mm, and the thickness of the driving active coating is 1μm~3μm; under the action of an applied voltage, the length of a single linear fiber changes, thereby producing an axial driven deformation of the helical structured piezoelectric chemical driven fiber.

[0033] When the layered fiber film is twisted or the equal-length linear fibers are twisted, electrolyte gel layers need to be attached to the front and back of the film respectively; the electrolyte gel layers include sulfuric acid gel or ion gel, so as to ensure the stability of the electrochemical reaction system.

[0034] The piezoelectric chemical driving fiber provided by the present invention has the characteristics of being stretchable and self-resetting; the deformation forms under the action of the driving voltage include elongation and shortening.

[0035] The second aspect of the present invention provides a method for preparing a piezoelectric chemically driven fiber, which is mainly aimed at forming a rod-shaped concentric winding structure by stacking layered fiber films, twisting and applying an electrochemical reaction system, and specifically comprises the following steps: A metal foil with a thickness of 6 μm to 10 μm is fixed in a vacuum chamber (1×10 -7 Torr~7×10 -7 On a rotating table of a 300-1000-torr, an inverted transition metal sulfide target is suspended opposite to the target, so that the target and the exposed surface of the metal foil are arranged facing each other with a spacing of 30 mm to 45 mm; the transition metal sulfide target is bombarded with a YAG pulse laser with a frequency of 1 Hz to 10 Hz to achieve a solid-plasma-solid phase transition and then deposited on the exposed surface of the metal foil for 10 h to 20 h; a transition metal sulfide film is prepared on the metal foil; 0.5 mol to 1 mol sulfuric acid-polyvinyl alcohol gel or 1-butyl-3-methylimidazolium hexafluorophosphate-polyvinylidene fluoride-hexafluoropropylene ion gel is uniformly coated on the transition metal sulfide film by using a coating machine with a rotation speed of 500 rpm to 10000 rpm; Then, 2 to 50 transition metal sulfide films coated with sulfuric acid-polyvinyl alcohol gel or 1-butyl-3-methylimidazolium hexafluorophosphate-polyvinylidene fluoride-hexafluoropropylene ion gel are stacked and arranged at equal angles along the center of the layout, and the films are twisted at a twist rate of 20 turns / m to 100 turns / m along the diagonal line of the arrangement layout; Subsequently, the rod-shaped concentric coiled layer structure fiber is immersed in 0.5 mol~1 mol sulfuric acid-polyvinyl alcohol gel or 1-butyl-3-methylimidazole hexafluorophosphate-polyvinylidene fluoride-hexafluoropropylene ion gel for 1h~2h, and then solidified in a 5℃~10℃ low-temperature box for 0.5h~1h to obtain a rod-shaped concentric coiled layer structure piezoelectric chemical drive fiber.

[0036] The third aspect of the present invention provides a method for preparing a piezoelectric chemically driven fiber, which is mainly aimed at forming a linear fiber spiral structure from a spinning solution through molding, twisting and applying an electrochemical reaction system; specifically comprising the following steps: Pour polyacrylonitrile or polyimide spinning stock solution into a decorating bag, select a decorating nozzle with the same outlet size according to the size of the original silk and place it at the front end of the decorating bag, squeeze the decorating bag to spray into a coagulation bath with a concentration of 30% to 60% and a temperature of 40°C to 65°C, and the silk is radially arranged spirally from the center of the coagulation bath to the outside; draw 3 to 5 times in a steam environment of 70°C to 80°C, and then perform a dense treatment in a high-temperature drying box of 85°C to 120°C for 2h to 5h to achieve the shaping of the original silk; The original silk coil was placed in a vacuum chamber (1×10 -7 Torr~7×10 -7 On a rotating table of a 300-torr, an inverted transition metal sulfide target is hung opposite to the target, so that the target and the precursor are arranged facing each other with a spacing of 40mm to 55mm; the transition metal sulfide target is bombarded with a YAG pulse laser with a frequency of 1Hz to 10Hz to achieve a solid-plasma-solid phase transition and then deposited on the exposed surface of the precursor for 8h to 15h; transition metal sulfide is obtained on the surface; Then, the vacuum chamber was opened, the coiled raw silk was turned over, and the vacuum degree was pumped down to 1×10 -7 Torr~7×10 - 7Torr, using a YAG pulse laser with a frequency of 1Hz~10Hz to bombard the transition metal sulfide target for 8h~15h; then take out the original silk with transition metal sulfide growing on the surface, cut it into silk segments with a length of 1cm~150cm, soak it in 0.5mol~1mol sulfuric acid-polyvinyl alcohol gel or 1-butyl-3-methylimidazole hexafluorophosphate-polyvinylidene fluoride-hexafluoropropylene ion gel for 1h~2h, and then solidify it in a 5℃~10℃ incubator for 0.5h~1h; 2 to 50 raw fibers coated with sulfuric acid-polyvinyl alcohol gel or 1-butyl-3-methylimidazolium hexafluorophosphate-polyvinylidene fluoride-hexafluoropropylene ion gel are arranged along the axis to form a raw fiber cluster, two ends of the raw fiber cluster are fixed respectively by two chucks, and a pre-stretching force is applied while twisting at a twist of 100 turns / m to 15,000 turns / m; Subsequently, the helical structure fiber is immersed in 0.5 mol~1 mol sulfuric acid-polyvinyl alcohol gel or 1-butyl-3-methylimidazole hexafluorophosphate-polyvinylidene fluoride-hexafluoropropylene ion gel for 1h~2h, and then solidified in a 5℃~10℃ incubator for 0.5h~1h to obtain a piezoelectric chemically driven fiber with a helical structure.

[0037] A fourth aspect of the present invention provides an application of a piezoelectric chemical drive fiber in an aircraft or a drive mechanism.

[0038] During the application process, the combined output of the deformation of two or more piezoelectric chemical driven fibers is used to control the angle of attack of the seeker, thereby controlling the flight attitude and trajectory of the micro-missile.

[0039] The driving deformation of the oppositely arranged piezoelectric chemical drive fibers is used to realize the high-speed movement of the mass slider at the center of mass of the warhead, thereby generating the variable center of mass mass moment control function of the missile. By changing the relative displacement of the center of mass and the aerodynamic pressure center of the missile during high-speed flight, the aerodynamic balancing moment or the offset of the main axis of inertia of the missile body is used to change the flight attitude of the missile, thereby realizing the maneuverability control of the missile and regulating its flight attitude and trajectory.

[0040] A fiber drive mechanism is composed of no less than three piezoelectric chemical drive fibers, which replace the traditional servo motor to provide fast-response driving force for the swing nozzle.

[0041] It should be noted that the experimental methods used in the present invention are all conventional methods unless otherwise specified; the reagents and materials used are all commercially available unless otherwise specified.

[0042] Example 1 The rod-shaped concentric winding structure is formed by stacking and twisting layered fiber films and applying an electrochemical reaction system; the specific preparation process is as follows Figure 1 As shown, first, a 10 μm thick aluminum foil is fixed in a vacuum chamber (1×10-7 On a rotating table of 1000 Torr, an inverted molybdenum disulfide target was hung opposite to it, so that the molybdenum disulfide target and the exposed surface of the aluminum foil were arranged facing each other with a spacing of 45 mm; the molybdenum disulfide target was bombarded with a YAG pulse laser with a frequency of 10 Hz to achieve a solid-plasma-solid phase transition and then deposited on the exposed surface of the aluminum foil for 20 hours; 1 mol sulfuric acid-polyvinyl alcohol gel was evenly coated on the molybdenum disulfide film using a coating machine with a rotation speed of 10000 rpm; Figure 2 As shown, 12 molybdenum disulfide films coated with sulfuric acid-polyvinyl alcohol gel were stacked at equal angles along the center of the layout, and the films were twisted with a twist of 100 turns / m along the diagonal of the arrangement layout; then the rod-shaped concentric coiled layer structure fiber was immersed in 1 mol sulfuric acid-polyvinyl alcohol gel for 2 hours, and the scanning electron microscope image of the sulfuric acid-polyvinyl alcohol gel was shown in Figure 3 As shown in the figure, its porous structure can ensure the rapid progress of the electrochemical reaction; after solidifying in a 5℃ low-temperature box for 1h, it can be used as a piezoelectric chemical driving fiber to achieve Figure 4 The function of regulating the attack angle of the micro missile seeker.

[0043] Example 2 The rod-shaped concentric winding structure is formed by stacking and twisting layered fiber films and applying an electrochemical reaction system. First, a tungsten foil with a thickness of 6 μm is fixed in a vacuum chamber (7×10 -7 On a rotating table of 1000 ft (1000 m) high, an inverted tungsten disulfide target was suspended opposite to the exposed surface of the tungsten foil, and the tungsten disulfide target and the exposed surface of the tungsten foil were arranged opposite to each other with a spacing of 30 mm. The tungsten disulfide target was bombarded with a YAG pulse laser with a frequency of 1 Hz to achieve a solid-plasma-solid phase transition and then deposited on the exposed surface of the tungsten foil for 10 h. A coating machine with a rotation speed of 500 rpm was used to evenly coat 1-butyl-3-methylimidazole hexafluorophosphate-polyvinylidene fluoride-hexafluoropropylene ion gel on the tungsten disulfide target. On a tungsten sulfide film; then, two tungsten disulfide films coated with 1-butyl-3-methylimidazole hexafluorophosphate-polyvinylidene fluoride-hexafluoropropylene ion gel are stacked at equal angles along the center of the layout, and the films are twisted with a twist of 20 turns / m along the diagonal of the arrangement layout; then, the rod-shaped concentric coiled layer structure fiber is immersed in 1-butyl-3-methylimidazole hexafluorophosphate-polyvinylidene fluoride-hexafluoropropylene ion gel for 1 hour, and then solidified in a 10°C low-temperature box for 0.5 hour to be used as a piezoelectric chemical drive fiber.

[0044] Example 3 The helical structure of the linear fiber is formed by the spinning solution through molding, twisting and applying an electrochemical reaction system; the specific preparation process is as follows Figure 5As shown, first, pour the polyacrylonitrile spinning stock solution into the decorating bag, select a decorating nozzle with an outlet size of 2mm and place it at the front end of the decorating bag, and squeeze the decorating bag to spray into a coagulation bath with a concentration of 30% and a temperature of 40°C. The spinnerets are arranged radially in a spiral from the center of the coagulation bath to the outside ( Figure 6 ); draw three times in a 70℃ steam environment, and then place the original silk in a high-temperature drying oven at 85℃ for 2h to achieve the original silk shaping; place the original silk in a spiral in a vacuum chamber (7×10 -7 On a rotating table of 1000 × 100 mm, an inverted molybdenum disulfide target was hung opposite to the original silk, so that the molybdenum disulfide target and the original silk were arranged opposite to each other with a spacing of 40 mm. The molybdenum disulfide target was bombarded with a YAG pulse laser with a frequency of 1 Hz to achieve a solid-plasma-solid phase transition and then deposited on the exposed surface of the original silk for 15 h. Then the vacuum chamber was opened, the spiral original silk was turned over, and the vacuum degree was pumped down to 7 × 10 -7 Torr, using a YAG pulse laser with a frequency of 1 Hz to bombard the molybdenum disulfide target for 15 hours; then taking out the original wire with molybdenum disulfide growing on the surface, cutting it into 1 cm long wire segments, soaking it in 0.5 mol sulfuric acid-polyvinyl alcohol gel for 2 hours, and then solidifying it in a 10°C low temperature box for 1 hour; Figure 7 As shown in the figure, two protofilaments coated with sulfuric acid-polyvinyl alcohol gel are arranged along the axis to form a protofilament cluster, and two ends of the protofilament cluster are fixed by two clamps respectively, and a pre-stretching force is applied while twisting at a twist of 15000 turns / m; then the helical structure fiber is immersed in 0.5 mol sulfuric acid-polyvinyl alcohol gel for 2 hours, and then solidified in a 10°C low temperature box for 1 hour to be used as a piezoelectric chemical drive fiber, realizing the following Figure 8 As shown, the piezoelectric chemical drive fibers arranged in opposite directions are used to change the relative displacement of the center of mass and the aerodynamic pressure center of the missile during high-speed flight, thereby realizing the maneuverability control of the missile and regulating its flight attitude and trajectory.

[0045] Example 4 The linear fiber spiral structure is formed by the spinning solution through molding, twisting and applying an electrochemical reaction system. First, the polyimide spinning solution is poured into the decorating bag, and a decorating nozzle with an outlet size of 8 mm is selected and placed at the front end of the decorating bag. The decorating bag is squeezed to spray into a coagulation bath with a concentration of 60% and a temperature of 65°C. The spindles are arranged radially in a spiral shape from the center of the coagulation bath. The fibers are stretched 5 times in a steam environment at 80°C, and then densely treated in a high-temperature drying oven at 120°C for 5 hours to achieve the shaping of the original fibers. The original fibers are placed in a vacuum chamber (1×10 -7On a rotating table of 1000 × 1000 mm, an inverted tungsten disulfide target was hung opposite to the original silk, so that the tungsten disulfide target and the original silk were arranged opposite to each other with a spacing of 55 mm. The tungsten disulfide target was bombarded with a YAG pulse laser with a frequency of 10 Hz to achieve a solid-plasma-solid phase transition and then deposited on the exposed surface of the original silk for 8 hours. Then the vacuum chamber was opened, the spiral original silk was turned over, and the vacuum degree was pumped down to 1×10 -7 Torr, a YAG pulse laser with a frequency of 10 Hz is used to bombard a tungsten disulfide target for 8 hours; then the original wire with tungsten disulfide grown on the surface is taken out, cut into a wire segment with a length of 150 cm, immersed in 1-butyl-3-methylimidazole hexafluorophosphate-polyvinylidene fluoride-hexafluoropropylene ion gel for 1 hour, and then solidified in a 5°C low temperature box for 0.5 hour; 50 original wires coated with 1-butyl-3-methylimidazole hexafluorophosphate-polyvinylidene fluoride-hexafluoropropylene ion gel are arranged along the axis to form a original wire cluster, and two ends of the original wire cluster are fixed respectively by two chucks, and a pre-stretching force is applied while twisting at a twist of 100 turns / m; then the spiral structure fiber is immersed in 1-butyl-3-methylimidazole hexafluorophosphate-polyvinylidene fluoride-hexafluoropropylene ion gel for 1 hour, and then solidified in a 5°C low temperature box for 0.5 hour to be used as a piezoelectric chemical drive fiber, forming as follows Fig. 9 The fiber drive mechanism shown provides a fast-response driving force for the oscillating nozzle.

[0046] Example 5 The rod-shaped concentric winding structure is formed by stacking and twisting layered fiber films and applying an electrochemical reaction system. First, a copper foil with a thickness of 8 μm is fixed in a vacuum chamber (4×10 -7 On a rotating table of 1000 Torr, an inverted molybdenum disulfide target was suspended opposite to it, so that the molybdenum disulfide target and the exposed surface of the copper foil were arranged facing each other with a spacing of 40 mm; the molybdenum disulfide target was bombarded with a YAG pulse laser with a frequency of 5 Hz, so that it was deposited on the exposed surface of the copper foil after achieving a solid-plasma-solid phase transition, and the deposition time was 15 hours; 0.5 mol sulfuric acid-polyvinyl alcohol gel was evenly coated on the molybdenum disulfide film using a coating machine with a rotation speed of 1000 rpm; then 50 molybdenum disulfide films coated with sulfuric acid-polyvinyl alcohol gel were stacked at equal angles along the center of the layout, and the films were twisted with a twist of 70 turns / m along the diagonal of the arrangement layout; then the rod-shaped concentric coiled layer structure fiber was immersed in 0.5 mol sulfuric acid-polyvinyl alcohol gel for 1.5 hours, and then solidified in a low-temperature box at 8°C for 0.8 hours to be used as a piezoelectric chemical drive fiber.

[0047] Example 6 The linear fiber spiral structure is formed by the spinning solution through molding, twisting and applying an electrochemical reaction system. First, the polyacrylonitrile spinning solution is poured into the decorating bag, and a decorating nozzle with an outlet size of 5 mm is selected and placed at the front end of the decorating bag. The decorating bag is squeezed to spray into a coagulation bath with a concentration of 50% and a temperature of 50°C. The spindles are arranged radially in a spiral shape from the center of the coagulation bath. Four stretchings are carried out in a 75°C steam environment, and then the original fibers are densely treated in a high-temperature drying oven at 100°C for 3 hours to achieve the shaping of the original fibers. The original fibers are spirally placed in a vacuum chamber (5×10 -7 On a rotating table of 1000 × 1000 Å, an inverted tungsten disulfide target was hung opposite to the original silk, so that the tungsten disulfide target and the original silk were arranged opposite to each other with a spacing of 45 mm. The tungsten disulfide target was bombarded with a YAG pulse laser with a frequency of 5 Hz to achieve a solid-plasma-solid phase transition and then deposited on the exposed surface of the original silk for 10 h. Then the vacuum chamber was opened, the spiral original silk was turned over, and the vacuum degree was pumped to 5 × 10 -7 Torr, a YAG pulse laser with a frequency of 5 Hz was used to bombard a tungsten disulfide target for 10 hours; then the protofilament with tungsten disulfide grown on the surface was taken out, cut into 50 cm long segments, immersed in 1 mol sulfuric acid-polyvinyl alcohol gel for 1.5 hours, and then solidified in a 7°C low temperature box for 0.75 hours; 30 protofilaments coated with sulfuric acid-polyvinyl alcohol gel were arranged along the axis to form a protofilament cluster, and two ends of the protofilament cluster were fixed respectively with two chucks, and a pre-stretching force was applied while twisting at a twist of 3000 turns / m; then the helical structure fiber was immersed in 1 mol sulfuric acid-polyvinyl alcohol gel for 1.5 hours, and then solidified in a 7°C low temperature box for 0.75 hours to be used as a piezoelectric chemical drive fiber.

[0048] In summary, the present invention discloses a piezoelectric chemical drive fiber, a preparation method and its application. The piezoelectric chemical drive fiber has a high-low voltage composite drive function, can produce drive deformation based on the inverse piezoelectric effect and the electrochemical drive effect under the action of an external electric field, improves the response speed, control accuracy and driving force of the drive fiber through the inverse piezoelectric drive effect, and ensures the deformation amplitude of the drive fiber under low drive voltage and low energy consumption conditions through the electrochemical drive effect. The piezoelectric chemical drive fiber of the present invention can realize the flight attitude and orbit control function of a micro-missile by adjusting the angle of attack of the seeker or the position of the mass slider of the center of mass of the missile body, and can also form a fiber drive system to control the engine vector nozzle to achieve directional output of thrust, thereby broadening its development and application in the field of attitude and orbit control engines and main engine technology.

[0049] The present invention describes preferred embodiments and their effects. However, those skilled in the art may make additional changes and modifications to these embodiments once they are aware of the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.

[0050] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A piezoelectric chemically driven fiber, characterized in that: It has high and low voltage composite driving function, combining ion embeddability effect and piezoelectric effect; it can realize efficient conversion of electric energy-chemical reaction-mechanical deformation based on electrochemical reaction under the action of -3V~3V driving voltage, and realize low voltage, low energy consumption, and large output displacement driving function; it can realize rapid conversion of electric energy-mechanical deformation based on inverse piezoelectric effect under the action of -20V~-3V and 3V~130V driving voltage, and realize high precision, fast response, large output force, and displacement proportional adjustment driving function.

2. The piezoelectric chemical driving fiber according to claim 1, characterized in that: It includes two or more sheets of layered fiber films stacked at equal distances or angles around the center of the arrangement, and twisted along the diagonal of the arrangement to form a rod-shaped concentric layer structure; Or a fiber with a helical structure formed by two or more linear fibers of equal length being twisted and rotated along the center of arrangement.

3. The piezoelectric chemical driving fiber according to claim 2, characterized in that: The initial length of the fiber with the rod-like concentric coil structure or the fiber with the linear fiber spiral structure is 1-150 cm, and the ratio of the deformed length to the initial length is (0.65-1.05):

1.

4. The piezoelectric chemical driving fiber according to claim 2, characterized in that: The layered fiber film includes a substrate and a driving active material attached to the substrate, wherein the substrate and the driving active material are tightly connected via a heterogeneous structure; the thickness ratio of the driving active material to the substrate is (0.7-2):

1.

5. The piezoelectric chemical driving fiber according to claim 4, characterized in that: The driving active material generates electrochemical driven deformation and reverse piezoelectric driven deformation under the action of an applied voltage, and the substrate does not generate deformation response to the applied voltage; The interaction between the substrate and the driving active material causes the rod-shaped concentric scroll structure to shrink, and after the applied voltage is removed, the structure returns to its original length; The substrate is a metal foil; the driving active material is a transition metal sulfide.

6. The piezoelectric chemical driving fiber according to claim 2, characterized in that: The linear fibers include polymer fibers and a driving active coating attached to the surface of the polymer fibers; The polymer fiber and the driving active coating are tightly connected via a heterogeneous structure; The polymer fiber has a diameter of 2 mm to 8 mm; The driving active coating has a thickness of 1 μm to 3 μm; The length of the linear fiber changes under the action of an external voltage, so that the fiber with a helical structure is driven to deform in the axial direction; wherein the driving active coating is a transition metal sulfide coating.

7. The piezoelectric chemical driving fiber according to claim 2, characterized in that: When the layered fiber film is twisted or the equal-length linear fibers are twisted, electrolyte gel layers need to be attached to the front and back of the film respectively; the electrolyte gel layers include sulfuric acid gel or ion gel.

8. A method for preparing the piezoelectric chemically driven fiber according to claim 2, characterized in that: The following steps are involved: A metal foil with a thickness of 6 μm to 10 μm is fixed on a rotating table in a vacuum chamber, and an inverted transition metal sulfide target is suspended opposite to the metal foil so that the target and the exposed surface of the metal foil are arranged facing each other with a spacing of 30 mm to 45 mm; the transition metal sulfide target is bombarded with a YAG pulse laser with a frequency of 1 Hz to 10 Hz to achieve a solid-plasma-solid phase transition and then deposited on the exposed surface of the metal foil for a deposition time of 10 h to 20 h; a transition metal sulfide film is obtained on the metal foil; 0.5 mol to 1 mol sulfuric acid-polyvinyl alcohol gel or 1-butyl-3-methylimidazolium hexafluorophosphate-polyvinylidene fluoride-hexafluoropropylene ion gel is uniformly coated on the transition metal sulfide film by using a coating machine with a rotation speed of 500 rpm to 10000 rpm; Then, 2 to 50 transition metal sulfide films coated with sulfuric acid-polyvinyl alcohol gel or 1-butyl-3-methylimidazolium hexafluorophosphate-polyvinylidene fluoride-hexafluoropropylene ion gel are stacked and arranged at equal angles along the center of the layout, and the films are twisted at a twist rate of 20 turns / m to 100 turns / m along the diagonal line of the arrangement layout; Subsequently, the rod-shaped concentric coiled layer structure fiber is immersed in 0.5 mol~1 mol sulfuric acid-polyvinyl alcohol gel or 1-butyl-3-methylimidazole hexafluorophosphate-polyvinylidene fluoride-hexafluoropropylene ion gel for 1h~2h, and then solidified in a 5℃~10℃ low-temperature box for 0.5h~1h to obtain a rod-shaped concentric coiled layer structure piezoelectric chemical drive fiber.

9. A method for preparing the piezoelectric chemically driven fiber according to claim 2, characterized in that: The following steps are involved: Pour polyacrylonitrile or polyimide spinning stock solution into a decorating bag, select a decorating nozzle with the same outlet size according to the size of the original silk and place it at the front end of the decorating bag, squeeze the decorating bag to spray into a coagulation bath with a concentration of 30% to 60% and a temperature of 40°C to 65°C, and the silk is radially arranged spirally from the center of the coagulation bath to the outside; draw 3 to 5 times in a steam environment of 70°C to 80°C, and then perform a dense treatment in a high-temperature drying box of 85°C to 120°C for 2h to 5h to achieve the shaping of the original silk; The precursor is placed on a rotating table in a vacuum chamber, and an inverted transition metal sulfide target is suspended opposite to the precursor, so that the target and the precursor are arranged facing each other with a spacing of 40mm to 55mm; the transition metal sulfide target is bombarded with a YAG pulse laser with a frequency of 1Hz to 10Hz to achieve a solid-plasma-solid phase transition and then deposited on the exposed surface of the precursor for 8h to 15h; transition metal sulfide is obtained on the surface; Then, the vacuum chamber was opened, the coiled raw silk was turned over, and the vacuum degree was pumped down to 1×10 -7 Torr~7×10 -7 Torr, using a YAG pulse laser with a frequency of 1Hz~10Hz to bombard the transition metal sulfide target for 8h~15h; then take out the original silk with transition metal sulfide growing on the surface, cut it into silk segments with a length of 1cm~150cm, soak it in 0.5mol~1mol sulfuric acid-polyvinyl alcohol gel or 1-butyl-3-methylimidazole hexafluorophosphate-polyvinylidene fluoride-hexafluoropropylene ion gel for 1h~2h, and then solidify it in a 5℃~10℃ incubator for 0.5h~1h; 2 to 50 raw fibers coated with sulfuric acid-polyvinyl alcohol gel or 1-butyl-3-methylimidazolium hexafluorophosphate-polyvinylidene fluoride-hexafluoropropylene ion gel are arranged along the axis to form a raw fiber cluster, two ends of the raw fiber cluster are fixed respectively by two chucks, and a pre-stretching force is applied while twisting at a twist of 100 turns / m to 15,000 turns / m; Subsequently, the helical structure fiber is immersed in 0.5 mol~1 mol sulfuric acid-polyvinyl alcohol gel or 1-butyl-3-methylimidazole hexafluorophosphate-polyvinylidene fluoride-hexafluoropropylene ion gel for 1h~2h, and then solidified in a 5℃~10℃ incubator for 0.5h~1h to obtain a piezoelectric chemically driven fiber with a helical structure.

10. Use of the piezoelectric chemical drive fiber according to any one of claims 1 to 7 in an aircraft or a drive mechanism.

Citation Information

Patent Citations

  • Artificial muscle fiber and artificial muscle

    CN107582214A

  • Electrochemically-driven artificial muscle fiber as well as preparation method and application thereof

    CN111826765A

  • Piezoelectric chemical fiber, preparation method and application thereof

    CN113497178B

  • Artificial muscle fiber as well as preparation method, application and driving test device thereof

    CN114150399A

  • Bionic neuromuscular fiber and preparation method and application thereof

    CN114790657A